Health Insurance and Consumption Risk - Lockwood, Lee M. (The Review of Economics and Statistics, 2026)
The effect of health insurance on consumption risk depends in part on how it interacts with other risks beyond health care cost risk, such as income risk. Using a variety of approaches, I find that for U.S. households, the interaction with other risks transforms the risk protection from health insurance. Standard contracts amplify the impact of other risks, due to both subsidizing normal goods and undoing the protection against other risks from discounts, charity care, and bad debt. Alternative contracts that account for other risks, such as contracts that limit out-of-pocket spending relative to income, can provide better risk protection.